Recommendations of a PIM impact evaluation are used to improve the Baraza program, implemented by Uganda's Office of the Prime Minister to enhance access to and effectiveness of public services - CGIAR Research Program on Policies, Institutions, and Markets (2020)
Recommendations of a PIM impact evaluation are used to improve the Baraza program, implemented by the Office of the Prime Minister to enhance access to and effectiveness of public services.